Shariah observation advertising practices of Bank Muamalat in Malaysia - Haque, A. K. M. Ahasanul; Mohd. Israil, Khaliq Ahmad; Irfath Jahan, Syeada (Emerald Publishing Group, 2010)
Purpose – The purpose of this paper is to assess the existing advertising practices in Malaysia and their compliance with the Shariah (Islamic Law). Design/methodology/approach – Using descriptive observations, the promotional tools and practices used by the prominent conventional banks were compared to those used by the Islamic banks. A total of 40 different advertisements were assessed as well as staff and personnel from 30 branches were interviewed. Findings – The paper reveals that customers remain unaware of the Islamic banks’ products. Shariah-based promotions will help increase customer awareness of these banks and their offerings. Research limitations/implications – Future research on Shariah-based promotions and advertising will improve banks’ effectiveness and help position themas rolemodels for other advertisers, both Islamic and non-Islamic.The producers of Islamic advertisements need to apply precise screening procedures that ensure the delivery of their message through Shariah-compliant methods. Originality/value – The paper contributes to research through improving understanding of the main issues relating to the effect of advertising practices in Islamic societies.